PENGARUH KOMPETENSI PROFESIONAL GURU GEOGRAFI TERHADAP HASIL BELAJAR SISWA SMA DI KABUPATEN PELALAWAN - Rediana Manurung, - (2021)
The achievement of high student learning outcomes cannot be separated from the role of teachers and students. The teacher's role is needed as a manager of the learning process that can affect student activities so that student learning outcomes are maximized. Therefore, it is necessary to have the support of teachers who have professional competence in learning geography. The purpose of this study is to analyze how much influence the professional competence of geography teachers in mastering basic competency standards, professional competence of geography teachers in mastering materials, structures, concepts, professional competence of geography teachers in developing learning materials creatively, professional competence of geography teachers in developing their professionalism in a sustainable manner by taking reflective action, teachers' professional competence in utilizing information and communication technology to take advantage of the school environment on student learning outcomes. The research method used in this study is a descriptive study method, using a quantitative approach. The population is geography teachers and students of class X IPS in SMA Pelalawan Regency totaling 34 teachers and 826 students. The number of samples used were 34 teachers of geography and 270 students of class X IPS. The test used is linear regression test. The results of this study are that there is an influence of professional competence of geography teachers in mastering basic competency standards (sig = 0,000) in mastering the material, structure, concept of utilizing the school environment (sig =0,000), developing learning materials creatively utilizing the surrounding environment (sig =0,000 ), develop their professionalism in a sustainable manner (sig =0,000), utilizing information and communication technology (sig = 0.047) on the learning outcomes of high school students in Pelalawan Regency. From the results of the simple linear regression test, the value of sig =0,000 can be concluded so that it can be concluded that there is an influence of teacher professional competence (X) on the learning outcomes of high school students in Pelalawan Regency. Keywords: Competence, Teacher's Professional Competence, School Environment, Student's Learning Outcomes Pencapaian hasil belajar siswa yang tinggi tidak terlepas dari peran guru dan siswa. Diperlukan peran guru sebagai pengelola proses pembelajaran yang dapat mempengaruhi aktifitas siswa sehingga hasil belajar siswa maksimal. Oleh sebab itu perlu adanya dukungan guru yang memiliki kompetensi profesional dalam pembelajaran geografi. Tujuan penelitian ini yaitu menganalisis seberapa besar pengaruh kompetensi profesional guru geografi dalam menguasai standar kompetensi dasar, kompetensi profesional guru geografi dalam menguasai materi, struktur, konsep, kompetensi profesional guru geografi dalam mengembangkan materi pembelajaran secara kreatif, kompetensi profesional guru geografi dalam mengembangkan keprofesionalnya secara berkelanjutan dengan melakukan tindakan reflektif, kompetensi profesional guru dalam memanfaatkan tehnologi informasi dan komunikasi terhadap hasil belajar siswa. Metode penelitian yang digunakan dalam penelitian ini adalah metode studi deskriptif, dengan menggunakan pendekatan kuantitatif. Populasi adalah para guru geografi serta peserta didik kelas X IPS di SMA Kabupaten Pelalawan berjumlah 34 guru dan 826 siswa. Jumlah sampel yang digunakan yaitu 34 guru geografi dan 270 siswa kelas X IPS. Uji yang digunakan yaitu uji regresi linier. Hasil penelitian ini yaitu ada pengaruh kompetensi profesional guru geografi dalam menguasai standar kompetensi dasar (sig=0,000) dalam menguasai materi, struktur, konsep (sig=0,000), mengembangkan materi pembelajaran secara kreatif memanfaatkan lingkungan sekitar (sig=0,000), mengembangkan keprofesionalnya secara berkelanjutan (sig=0,000), memanfaatkan tehnologi informasi dan komunikasi (sig=0,047) terhadap hasil belajar siswa SMA di Kabupaten Pelalawan. Dari hasil uji regresi linier sederhana didapatkan nilai sig=0,000 sehingga dapat disimpulkan bahwa ada pengaruh kompetensi profesional guru (X) terhadap hasil belajar siswa SMA di Kabupaten Pelalawan. Kata Kunci : Kompetensi, Kompetensi Profesional Guru, Hasil Belajar Siswa